Prosperity gospel: A missiological assessement - Gbote, Eric Z. M. (HTS teologiese studies, 2014)
The article attempts to establish that prosperity gospel is rooted in the faulty interpretation of several biblical passages. The prosperity gospel portrays wealth and riches as a covenant and the fulfilment of the divine promise of God to his people. The basic teaching of the prosperity gospel is that God wants believers to get rich or healthy, but he cannot bless them unless they first send money known as ‘seed-faith’ to their spiritual leader or pastor who tells them about the plan. This approach was popularised by the American televangelist Oral Roberts in Tulsa Oklahoma in the United States of America (USA). It has now spread to other parts of the world, including Africa. This article investigates the teaching of this theology whilst attempting to offer a biblical foundation of Christian giving for the work of God.